2018
DOI: 10.1186/s12936-018-2275-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 15-month multi-channel continuous distribution pilot on ITN ownership and access in Eastern Region, Ghana

Abstract: BackgroundInsecticide-treated nets are a key intervention for malaria prevention. While mass distribution can rapidly scale up ITN coverage, multiple channels may be needed to sustain high levels of ITN access and ownership. In Ghana’s Eastern Region, a continuous ITN distribution pilot, started in October 2012, 18–24 months after a mass campaign. The pilot distributed ITNs through antenatal care services (ANC), child welfare clinic services (CWC) through the Expanded Programme on Immunization, and to students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This high ownership of LLINs in households is obviously due to the free mass distribution of LLINs immediately before the study commenced. In the Eastern Region of Ghana, 91.3% ownership was found after thirty-one months post-distribution of LLINs [23]. Based on individual household ownership levels, it is important for the National Malaria Control Programme of Ghana to begin plans for LLINs distributions after a one-year post distribution of free mass campaigns as bed net ownership begins to effectively change after 12 months postdistribution.…”
Section: Discussionmentioning
confidence: 99%
“…This high ownership of LLINs in households is obviously due to the free mass distribution of LLINs immediately before the study commenced. In the Eastern Region of Ghana, 91.3% ownership was found after thirty-one months post-distribution of LLINs [23]. Based on individual household ownership levels, it is important for the National Malaria Control Programme of Ghana to begin plans for LLINs distributions after a one-year post distribution of free mass campaigns as bed net ownership begins to effectively change after 12 months postdistribution.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous distribution of ITNs through health facilities serves as a primary channel for maintaining ITN access that is achieved through triennial ITN mass distributions and ensuring continuous access to ITNs for pregnant women and children under one year of age. In Ghana, continuous distribution of ITNs through health facilities has been implemented in all districts since 2012 through distribution of ITNs to pregnant women receiving ANC and children receiving the Measles-Rubella Vaccine 2 (MR2) at EPI services (through child welfare clinics [CWCs]) [ 4 ]. There have also been four rounds of mass ITN distribution campaigns since 2010.…”
Section: Introductionmentioning
confidence: 99%
“…More countries are beginning to implement CD of nets through schools and communities (through local political/community leaders). School-based distributions have been evaluated in Ghana, Tanzania, and Nigeria [36][37][38][39] and community distribution programmes have been successfully piloted in a number of locations, including Madagascar, South Sudan, and Zanzibar [40,41].…”
mentioning
confidence: 99%
“…The financial cost for the community-based CD program was reported to be 19.21 USD (18.81 USD when deflated to 2017 USD) per net distributed. Studies estimating the cost of delivering nets through school-based distribution programs were not identified in the literature, though a small number of studies were identified that evaluated the effects of these systems on net ownership and access [36][37][38][39]. As countries continue to scale up combination delivery systems, they will require information on the costs of these various distribution channels, as well as information about how these costs relate to other outcomes, such as coverage and malaria incidence.…”
mentioning
confidence: 99%